1992
DOI: 10.2172/7103035
|View full text |Cite
|
Sign up to set email alerts
|

Mainstem Clearwater River study: Assessment for Salmonid Spawning, Incubation, and Rearing.

Abstract: our fishery technicians, subjected themselves to long work days and physically trying weather conditions. Kendall Jackson provided additional field assistance when called upon. David Statler provided valuable technical assistance and reviewed manuscripts. John Knutzen, Scott Wilcox, and Ken Winnick assisted during the collection of hydraulic crosssection data and Lisa Russel summarized and entered these data into data base format. Vance Penton assisted in designing and fabricating our freeze-core equipment. Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…The emergence date of each fish was back calculated based on fork length at capture, mean observed growth rate (W. P. Connor, unpublished data), and a mean fork length of 38 mm at emergence (Arnsberg et al 1992). The data was grouped into three cohorts per year to approximate the life history of fish from the three spawning areas described previously.…”
Section: Discussionmentioning
confidence: 99%
“…The emergence date of each fish was back calculated based on fork length at capture, mean observed growth rate (W. P. Connor, unpublished data), and a mean fork length of 38 mm at emergence (Arnsberg et al 1992). The data was grouped into three cohorts per year to approximate the life history of fish from the three spawning areas described previously.…”
Section: Discussionmentioning
confidence: 99%
“…Dworshak Dam lacks fish passage, resulting in the permanent loss of productive salmonid spawning aggregates and high quality habitat. The lower Clearwater River temperature regime continues to be altered by Dworshak Dam, resulting in warmer water in the winter and cooler water in the summer (Arnsberg et al 1992, Arnsberg andStatler 1995).…”
Section: History and Status Of Clearwater River Subbasin Coho Salmon mentioning
confidence: 99%
“…The fish component of the mainstem Clearwater River has been evaluated in recent studies by the Nez Perce Tribe (Connor, 1989, andArnsberg, et al, 1992). Connor (1 989) reported that, in 1989, chinook parr were uncommon.…”
Section: Warm Springsmentioning
confidence: 99%